(untitled) (Revista de Medicina Clinica, 2025)
Epilepsy is one of the more common neurological disease in humans; in children, it affects about 1%. In childhood, epilepsy can interfere with brain development, resulting in major cognitive disorders. Many factors can influence the cognitive prognosis of children with epilepsy, the age of onset being one of the most determining variables. The presence of neurodevelopmental comorbidities and polytherapy are related to a worse prognosis. The neuropathology of epilepsy produces a reorganization of language circuits with diminished functional connectivity. It also alters the networks and white matter tracts that are involved in both language and social behavior and cognition. Memory processes are particularly vulnerable to the effects of interictal epileptiform discharges, altering both verbal and nonverbal memory in the short and long term. Some epileptic syndromes occur during periods of vulnerability in brain maturation, interfering with the development of specific cognitive functions. Antiepileptics reduce neuronal irritability, but also reduce excitability and, therefore, can alter cognition. The primary effects of antiepileptics on cognition include reduced psychomotor processing speed, sustained attention and learning. An early assessment of neurodevelopmental comorbidities can facilitate treatment decisions by providing prognostic information about seizures, as well as comorbidity treatment.